Karakter Kebijakan Luar Negeri Indonesia - Yuwan Julianingtias (Universitas Dehasen Bengkulu, 2024)
This paper describes the background of the foreign policy used by Indonesia during the Soekarno era as a new country in the international world. Where this matter is also a factor that affects how the implementation of Indonesia's foreign policy in the future. As for the matter in this case, namely, when Sukarno and Hatta were proclaimed Indonesian independence on 17 August 1945, which was considered to be the beginning of the Indonesian revolution. After independence, various kinds of implementation of Indonesia's foreign policy were welcomed and fully supported by its people. However, in the course of history, due to the elitism of the Soeharto era, Indonesia's foreign policy has also been elitism. Almost all policies were carried out and centralized by Suharto, so that Indonesia's foreign policy was unstructured and not well distributed among related institutions. Changes in the political system in the reform era since the fall of President Soeharto created opportunities to reform Indonesia's foreign policy. This paper is intended to examine the crises and challenges of Indonesia's foreign policy before and after Soeharto's New Order. This paper will also explain that since the fall of Soeharto, Indonesian diplomacy has played a substantive role in facing challenges in the social, economic and political fields that threaten the